Pre-eclampsia and risk of dementia later in life: nationwide cohort study. (17th October 2018) - Basit, Saima; Wohlfahrt, Jan; Boyd, Heather A
Abstract: Objective: To explore associations between pre-eclampsia and later dementia, overall and by dementia subtype and timing of onset. Design: Nationwide register based cohort study. Setting: Denmark. Population: All women with at least one live birth or stillbirth between 1978 and 2015. Main outcome measure: Hazard ratios comparing dementia rates among women with and without a history of pre-eclampsia, estimated using Cox regression. Results: The cohort consisted of 1 178 005 women with 20 352 695 person years of follow-up. Women with a history of pre-eclampsia had more than three times the risk of vascular dementia (hazard ratio 3.46, 95% confidence interval 1.97 to 6.10) later in life, compared with women with no history of pre-eclampsia. The association with vascular dementia seemed to be stronger for late onset disease (hazard ratio 6.53, 2.82 to 15.1) than for early onset disease (2.32, 1.06 to 5.06) (P=0.08). Adjustment for diabetes, hypertension, and cardiovascular disease attenuated the hazard ratios only moderately; sensitivity analyses suggested that body mass index was unlikely to explain the association with vascular dementia. In contrast, only modest associations were observed for Alzheimer's disease (hazard ratio 1.45, 1.05 to 1.99) and other/unspecified dementia (1.40, 1.08 to 1.83). Conclusions: Pre-eclampsia was associated with an increased risk of dementia, particularly vascular dementia. Cardiovascular disease, hypertension, and diabetes were unlikely to mediate the associations substantially, suggesting that pre-eclampsia and vascular dementia may share underlying mechanisms or susceptibility pathways. Asking about a history of pre-eclampsia could help physicians to identify women who might benefit from screening for early signs of disease, allowing for early clinical intervention.